PERSEPSI PETANI SISTEM INTEGRASI TERHADAP PERAN LEMBAGA PENJAMIN DAN PENANGGUNG RESIKO DI KECAMATAN KERUMUTAN KABUPATEN PELALAWAN - Neli Winda Sari; Susy Edwina; Yeni Kusumawaty (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Integrated agriculture or integrated agriculture are agricultural activities undertaken by involving or integrating agriculture in a broad sense. Cattle and Palm Oil Integration System (SISKA) is a combination of palm oil plantation management with cattle where palm oil bark is used as animal feed while livestock manure is used as a source of organic fertilizer and biogas. which aims to improveefficiency and productivity of agricultural land.so as to increase the greater revenue. This research is conducted in Kecamatan Kerumutan Pelalawan Regency which aims to know the perception of farmers on the role of the guarantor institution and the risk bearer in supporting the SISKA program. the study was conducted from June to November 2017 using survey method and census sampling technique to 5 groups of farmers applying SISKA with total of 62 farmers. Data analysis using Likert's scale. the result of the research shows that the perception of farmers on the role of the guarantor institution and the overall risk bearers is 1.98 that is in the less important category.Keywords: institution, risk, role, perception, system integration